2008
DOI: 10.1371/journal.pgen.1000301
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Interactions between Sir3p and the Nucleosomal LRS Surface Imply Their Direct Interaction

Abstract: The previously identified LRS (Loss of rDNA Silencing) domain of the nucleosome is critically important for silencing at both ribosomal DNA and telomeres. To understand the function of the LRS surface in silencing, we performed an EMS mutagenesis screen to identify suppressors of the H3 A75V LRS allele. We identified dominant and recessive mutations in histones H3, H4, and dominant mutations in the BAH (Bromo Adjacent Homology) domain of SIR3. We further characterized a surface of Sir3p critical for silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…If H3 K79 methylation were critical in antagonizing silencing, then the H3 K79R mutant would be expected to phenocopy dot1Δ cells with respect to the kinetics of silencing. For comparison, mutating H3 K79 to alanine abrogates silencing potentially by disrupting the charge-based interaction between either H3 and Sir3 or H3 and H4 (32,44). We replaced plasmids carrying HHT2::HHF2 alleles with plasmids carrying the appropriate K79R mutation (hht2K79R::HHF2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If H3 K79 methylation were critical in antagonizing silencing, then the H3 K79R mutant would be expected to phenocopy dot1Δ cells with respect to the kinetics of silencing. For comparison, mutating H3 K79 to alanine abrogates silencing potentially by disrupting the charge-based interaction between either H3 and Sir3 or H3 and H4 (32,44). We replaced plasmids carrying HHT2::HHF2 alleles with plasmids carrying the appropriate K79R mutation (hht2K79R::HHF2).…”
Section: Resultsmentioning
confidence: 99%
“…First, Dot1 catalyzes the mono-, di-, and trimethylation states of H3 K79 (27,28,30,31). This particular lysine is located on the loss of rDNA silencing (LRS) face of H3, a surface whose electrostatic properties are important for association between the nucleosome and the BAH domain of Sir3 (32)(33)(34)(35)(36). H3 K79 methylation, therefore, interferes with the nucleosome's ability to adequately bind Sir3 (9).…”
mentioning
confidence: 99%
“…Genetic suppressor studies over the course of many years suggested that the domain mediates binding of nucleosomes. Mutations that mapped to the BAH domain suppressed mutations of either the H4 tail or a patch on the nucleosome surface known as the LRS domain (Johnson et al 1990;Thompson et al 2003;Norris et al 2008;Sampath et al 2009). The BAH domain was sufficient for partial silencing when forced to dimerize, strengthening the notion that the BAH domain was sufficient for nucleosome recognition (Connelly et al 2006).…”
Section: Sir3 Protein Structurementioning
confidence: 99%
“…Obtaining cocrystals required the use of a SIR3 hypermorphic allele D205N, which suppresses silencing defects caused by mutations in histones and other silencing factors (Johnson et al 1990;Liu and Lustig 1996;Norris et al 2008). The mutation increases the affinity of Sir3 for nucleosomes in vitro (Connelly et al 2006).…”
Section: Histone Binding By Sir3 Bah Domainmentioning
confidence: 99%
“…Sir2p, which does not bind chromatin directly, is a histone deacetylase responsible for the hypoacetylation of histones in heterochromatin (Moazed 2001). Sir3p and Sir4p interact with the amino (N)-terminal tails of histones H3 and H4, and Sir3p also binds a region called LRS (loss of rDNA silencing) on the solvent-accessible surface of the nucleosome (Hecht et al 1995;Park et al 2002;Liou et al 2005;Norris et al 2008;Sampath et al 2009). These interactions are believed to be key to the binding/propagation of SIR complex along chromatin.…”
mentioning
confidence: 99%